Meta-Analysis of Scientific Articles According to Statistical Criteria: A Case Study in WSCAD - Osorio, Alessander; Dias, Marina; Cavalheiro, Gerson Geraldo H. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2018)
This paper presents the systematization of the results of the metaanalysis of the publications of the 18 editions of the WSCAD according to the categories: statistics, metrics and tests. The goal is not to invalidate the results, but to alert to how they are described and presented.From a sample of 426 publications, 93 % referred at least one of the terms searched, showing that there is some care in the demonstration of results, even inadequate or incomplete given the low occurrence of only 3 % of statistical tests confirmed by a second sample of 30 articles. It is necessary not only to focus on the development of the research object itself, but also on the results demonstrations.